2018
DOI: 10.1103/physrevfluids.3.063304
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of thermal counterflow in He II using particle tracking velocimetry

Abstract: Flow visualization using PIV (particle image velocimetry) and particularly PTV (particle tracking velocimetry) has been applied to thermal counterflow in He II for nearly two decades now, but the results remain difficult to interpret because tracer particle motion can be influenced by both the normal fluid and superfluid components of He II as well as the quantized vortex tangle. For instance, in one early experiment it was observed (using PTV) that tracer particles move at the normal fluid velocity v n , whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
46
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 64 publications
6
46
2
Order By: Relevance
“…The value of ∆v n,x increases with V n , keeping ∆v n,x > ∆v n,y . These results are consistent with the PTV experiments [33,34]. The present values are less than those of the experiments.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The value of ∆v n,x increases with V n , keeping ∆v n,x > ∆v n,y . These results are consistent with the PTV experiments [33,34]. The present values are less than those of the experiments.…”
supporting
confidence: 92%
“…Marakov et al visualized the velocity profile of the normal fluid by using He * 2 molecules [30], and the characteristic energy spectra were analyzed [31,32]. A particle tracking velocimetry (PTV) experiment provides insights on statistical properties and indicated that the velocity fluctuations of the normal fluid are anisotropic in contrast to classical fluid [33,34]. The result implies that QT makes the normal fluid fluctuate anisotropically.…”
mentioning
confidence: 99%
“…Recently, we studied particle motion in thermal counterflow across a wide heat flux range using PTV, and found that, indeed, particles moving under the influence of relatively high heat flux, to which we give the name G3, are constantly affected by both the normal fluid and vortex lines. However, for relatively low heat flux, we devised a scheme for analyzing the kinematics of particles entrained by the normal fluid, to which we give the name G2, separately from those trapped on vortices, which we call G1 [18]. Using this separation scheme, we proposed a simple estimation of the mean free path of G2 particles through the vortex tangle, we showed that G1 velocity fluctuations are likely caused by fluctuations of the local vortex line velocity, and we showed that power-law tails in transverse particle velocity probability density functions (PDFs) are due entirely to G1.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in the experimental techniques, including flow visualization [22][23][24] , as well as increasing computing power, renewed the interest to the spatial inhomogeneity due to presence of channel walls 19,[25][26][27][28][29][30][31] and spatially-resolved investigations of the transient behavior in the thermal counterflow 32 . The latter work showed that the vortex tangle that eventually fills the whole channel, grows starting from a number of remnant vortex rings.…”
Section: Introductionmentioning
confidence: 99%